HTML & XHTML: The Definitive Guide, 5th Edition - Kennedy, Bill (O'Reilly, 2011)
HTML & XHTML: The Definitive Guide, 5th Edition is the most comprehensive, up-to-date book available on HTML and XHTML. The authors cover every element of HTML/XHTML in detail, explaining how each element works and how it interacts with other elements. With hundreds of examples, the book gives you models for writing your own effective web pages and for mastering advanced features like style sheets and frames.